Un espace social transnational entre les Émirats et le sud de l’Iran : les Khodmouni (Lârestâni) à Dubaï - Amin Moghadam (EchoGéo)
The region of Lârestân, in the south of Iran, maintained continuous relations with the southern shore of the Persian Gulf well before the 20th century, most notably in the form of transnational migratory flows. On the creation of the United Arab Emirates state in 1971, the present migrants were granted the new state’s nationality and citizenship, while the new migrants, remained “temporary workers” because of policies restricting access to Emirati nationality. This paper will attempt to explore transnational dynamics engaged by the Lârestâni community and their impact in the home country.